Investigation of residual stress in lead-free BNT-based ceramic/ceramic composites. (15th April 2018) - Ayrikyan, Azatuhi; Prach, Olena; Khansur, Neamul H.; Keller, Stephanie; Yasui, Shintaro; Itoh, Mitsuru; Sakata, Osami; Durst, Karsten; Webber, Kyle G.
Abstract: Ceramic/ceramic composite structures have been proposed as a method for optimizing the electromechanical response of lead-free ferroelectrics. Co-sintering of ceramic composites, however, results in internal residual stresses as well as interdiffusion. In this investigation, the interaction between a nonergodic relaxor ferroelectric 0.93(Bi1/2 Na1/2 TiO3 )-0.07BaTiO3 and an ergodic relaxor ferroelectric 0.94Bi1/2 (Na0.78 K0.22 )1/2 TiO3 -0.06BiAlO3 in a multilayered composite structure is presented. The interaction between the two end members was analyzed both chemically and mechanically. The interdiffusion was characterized by EDX measurements and directly compared to the local mechanical properties as determined by nanoindentation. Vickers indentation was used to demonstrate the internal residual stresses through the indentation crack length anisotropy. Mechanical and chemical data are contrasted to a micro-XRD analysis, which reveals a change in the crystal structure of both end-members, most likely due to changes in the A-site elements as a result of interdiffusion. Graphical abstract: Image 1